Power Pondok Pesantren dalam Mempengaruhi Kebijakan Alokasi Dana Keistimewaan - Lestari, Umi Fitriana; Saputra, Wendi Aji (Jurnal Publisitas, 2023)
Privileges funds are funds provided by the state as consequence of the state's recognition of the privileges of Yogyakarta based on Law Number 13 of 2012 concerning Privileges of the Special Region of Yogyakarta. In general, the privilege fund is intended for five things, one of which is education and culture. This study aims to determine the power of the Al-munawwir Krapyak Islamic Boarding School in influencing the policy of allocation of privileged funds. Qualitative research methods, with supervision and investigation that are sharply described in analyzing and obtaining data on problems that occur in a group. The result of the research is that the power of Al-Munawwir Krapyak Islamic Boarding School, Islamic boarding school in influencing the policy of allocation of privileged funds is indicated by informal pressure on the government, especially the Yogyakarta Palace to place the pesantren as a cultural institution. Islamic boarding schools as cultural institutions have the right to access privilege funds as stated that culture is one of the areas that receive budget items from privilege funds, one of which was during a discussion with GKR Hemas at Keraton Kilen Yogyakarta. The effectiveness of the power of the Al-Munawwir Krapyak Islamic boarding school in influencing the policy of the allocation of privileged funds was quite effective, because it was directly related to the Yogyakarta Keraton elite. However, from the pesantren side there is no further escort at the execution stage of the policy makers. In fact, in the process of making this funding policy, it is necessary to have an escort so that the aspirations of the pesantren community come out or are included in the Danais budget.